IDENTIFIKASI HAZARD PADA AKTIVITAS PERKULIAHAN DI WORKSHOP POLITEKNIK GAJAH TUNGGAL - Anjas Dwi Hermawan (Fakultas Rekayasa dan Teknologi Industri, 2025)
This study aims to identify safe work steps, identify potential hazards, and preventive measures against lecture activities in a single elephant polytechnic workshop using the Job Safety Analysis (JSA) method. Workshops that are the center of practice learning face various safety risks, such as from work tools, chemicals, to environmental conditions. Observation was carried out in five main processes: Lathe, Las, Sitting Grinding, Hand Grinding, and Milling. The observation process produces 35 potential hazards. This danger is anticipated through control steps such as the use of personal protective equipment (PPE), technical improvement, and administrative management. These steps are used to create a safer learning environment, increase awareness of the importance of safety, and support the optimal learning process.